tDCS-Induced Memory Reconsolidation Effects and Its Associations With Structural and Functional MRI Substrates in Subjective Cognitive Decline - Vaqué-Alcázar, Lídia; Mulet-Pons, Lídia; Abellaneda-Pérez, Kilian; Solé-Padullés, Cristina; Cabello-Toscano, María; Macià, Dídac; Sala-Llonch, Roser; Bargalló, Nuria; Solana, Javier; Cattaneo, Gabriele; Tormos, José M.; Pascual-Leone, Alvaro; et al. (Frontiers in Aging Neuroscience, 2021)
Previous evidence suggests that transcranial direct current stimulation (tDCS) to the left dorsolateral prefrontal cortex (l-DLPFC) can enhance episodic memory in subjects with subjective cognitive decline (SCD), known to be at risk of dementia. Our main goal was to replicate such findings in an independent sample and elucidate if baseline magnetic resonance imaging (MRI) characteristics predicted putative memory improvement. Thirty-eight participants with SCD (aged: 60-65 years) were randomly assigned to receive active (N=19) or sham (N=19) tDCS in a double-blind design. They underwent a verbal learning task with 15 words (DAY-1), and 24h later (DAY-2) stimulation was applied for 15 min at 1.5 mA targeting the l-DLPFC after offering a contextual reminder. Delayed recall and recognition were measured one day after the stimulation session (DAY-3), and at 1-month follow-up (DAY-30). Before the experimental session, structural and functional MRI were acquired. We identified a group*time interaction in recognition memory, being the active tDCS group able to maintain stable memory performance between DAY-3 and DAY-30. MRI results revealed that individuals with superior tDCS-induced effects on memory reconsolidation exhibited higher left temporal lobe thickness and greater intrinsic functional connectivity within the default-mode network. Present findings confirm that tDCS, through the modulation of memory reconsolidation, is capable of enhancing performance in people with self-perceived cognitive complaints. Results suggest that SCD subjects with more preserved structural and functional integrity might benefit from these interventions, promoting maintenance of cognitive function in a population at risk to develop dementia.